Dietary catering and its effectiveness combined with physical exercise - Juraszek, Karolina; Kalisz, Zdzisława; Krzyżaniak, Joanna; Kucharczuk, Magda; Molska, Barbara (Journal of Education, Health and Sport, 2019)
Introduction: Proper nutrition benefits affect the health of the body. Throughout the world, you can observe the prevailing trend for physical exercise, healthy eating and active lifestyle. There are a lot of publications and books about dietetics, physical activity and selected diets.The aim of a study: The aim of the presented work was concerning the effects of catering diet combined with physical exertion, by customers catering for " Perfect Housewife " based in Ostrów Wielkopolski, Poland. Material and methods: A hundred people using dietary catering were asked about the re¬sults of the service. The relation between dietary catering and physical activity, sex, place of resi-dence and having food intolerance were evaluated. Conclusions: 1. Results of dietary catering are better when it is combined with physical ac-tivities. 2. Men have better mood more often and residents of towns from 20 to 100 thousands inhabitants have better medical examinations results as a consequence of using dietary cater-ing. 3. Food intolerance have no influence on the efficacy of using dietary catering.